Experimentally Calibrated Analysis of the Electronic Structure of CuO+: Implications for Reactivity. Issue 52 (28th November 2018) - Srnec, Martin; Navrátil, Rafael; Andris, Erik; Jašík, Juraj; Roithová, Jana
Abstract: The CuO + core is a central motif of reactive intermediates in copper‐catalysed oxidations occurring in nature. The high reactivity of CuO + stems from a weak bonding between the atoms, which cannot be described by a simple classical model. To obtain the correct picture, we have investigated the acetonitrile‐ligated CuO + ion using neon‐tagging photodissociation spectroscopy at 5 K. The spectra feature complex vibronic absorption progressions in NIR and visible regions. Employing Franck–Condon analyses, we derived low‐lying triplet potential energy surfaces that were further correlated with multireference calculations. This provided insight into the ground and low‐lying excited electronic states of the CuO + unit and elucidated how these states are perturbed by the change in ligation. Thus, we show that the bare CuO + ion has prevailingly a copper(I)‐biradical oxygen character. Increasing the number of ligands coordinated to copper changes the CuO + character towards the copper(II)‐oxyl radical structure. Abstract : Excited CuO : Franck–Condon analysis of vibrationally resolved photodissociation uncovered the complex structure of acetonitrile‐supported CuO + species with several triplet excited states. Benchmarked multireference theoretical calculations explain how the character of the Cu−O bond shifts from copper(I)‐oxygen towards copper(II)‐oxyl in ligated systems.